A better way to classify the Rhinectomy defect. Issue 1 (January 2022) - Gilhooly, Michael; Visavadia, Bhavin
Abstract : Introduction: The classification proposed (HVD), is based on dividing the external nose into a grid of nine squares by two horizontal lines (H Upper and H Lower) and two vertical lines (V Left and V Right), dividing the nose into horizontal and vertical thirds. The nose is composed of 3 layers (Depths), external skin (D1), the nasal skeleton (D2), and nasal lining (D3), and any one of these layers if excised should be reconstructed. The nine grid squares and three depths result in a total of 27 subsites which can be recorded in the notation format H (123), V(RML), D(123) according to the extent of tissue excised. Tumours extending beyond the external nose are characterised with the letter E. Methods: Case note review of resections of the external nose for squamous cell carcinoma requiring excision of the osteo-cartilaginous skeleton (n = 12) Results: patients with Extension (E) and 1 treated for tumour recurrence died during follow up. Conclusions: All patients in the cohort preferred autogenous to prosthetic reconstruction. The Forehead Flap is ideal for reconstruction of the skin (D1) and nasal vestibule (D3). Costochondral grafts are unreliable for reconstruction (D2) when adjunctive radiotherapy is administered and vascularised bone is preferred. Tumours with extension (E) have a poor prognosis. The HVD classification is adaptable to clinical practice, accurately describes the rhinectomy defect and lends itself to database storage for audit and research purposes. Whilst primarily designed for tumour cases, the HVD classification can be adopted for all causes of nasal tissue loss.